2010
DOI: 10.1177/1740774509356575
|View full text |Cite
|
Sign up to set email alerts
|

Principles for defining adverse events in behavioral intervention research: lessons from a family-focused adolescent drug abuse trial

Abstract: Background Behavioral intervention research has lagged behind biomedical research in developing principles for defining, categorizing, identifying, reporting, and monitoring adverse events and unanticipated problems. Purpose In this article we present a set of principles for defining adverse events and how they were applied in a large national multi-site family therapy study for substance-using adolescents, The Brief Strategic Family Therapy (BSFT™) Effectiveness Study. Methods The BSFT™ Effectiveness stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 27 publications
0
45
0
3
Order By: Relevance
“…One reason for this could be that psychological interventions often are considered to be safe, and consequently researchers might not prioritize monitoring of harms. In addition, there is a lack of clear guidelines on how to define, categorize, identify and report harms within this research field [15,16].…”
Section: American Psychological Association's Working Group On Journamentioning
confidence: 99%
“…One reason for this could be that psychological interventions often are considered to be safe, and consequently researchers might not prioritize monitoring of harms. In addition, there is a lack of clear guidelines on how to define, categorize, identify and report harms within this research field [15,16].…”
Section: American Psychological Association's Working Group On Journamentioning
confidence: 99%
“…Such systematic tracking and reporting of adverse events in psychosocial, behavioral intervention and observational studies is a more recent phenomenon, with guidelines being less clearly defined and a greater challenge to apply, as they were traditionally developed for biomedical research (3, 4). Consequently, the EMCs for our studies also considered the potential risks, both study-related and incidental to data collection, and provided feedback on the monitoring plans, their conduct and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The NIH also suggests that independent oversight may be indicated for Phase I or II trials, psychosocial, behavioral intervention and observational studies, particularly if vulnerable subjects, e.g., minors, are included or there are other significant risks to study participants (24, 6–8). Yet, there is limited guidance for the development and implementation of monitoring plans and oversight committees for psychosocial research (3, 4, 8). Several research groups have reported that the traditional DSMB model is inadequate or impractical in psychosocial, behavioral intervention and observational studies (24, 9).…”
mentioning
confidence: 99%
“…9,10,49 En el tratamiento de las adicciones y de otros trastornos de la salud mental los pacientes tienen un alto riesgo de presentar afecciones renales, cardiacas o respiratorias e infecciones asociadas al consumo; así como accidentes, conductas sexuales de riesgo, comportamiento violento o problemas con la ley debidos al abuso de sustancias; además de una exacerbación de la sintomatología psiquiátrica, o incluso conductas suicidas, causadas por el consumo de alcohol o de drogas 1,5,8,15,50,51 o dificultades en el funcionamiento familiar, laboral o social del sujeto. 52 La conducción de un ECCA debe contemplar un plan acorde para la identificación, evaluación, seguimiento y reporte de posibles eventos adversos. Los mecanismos o herramientas que se utilicen para llevar a cabo este monitoreo de seguridad deberán ser parte del protocolo de investigación.…”
Section: Monitoreo De Seguridadunclassified
“…Los mecanismos o herramientas que se utilicen para llevar a cabo este monitoreo de seguridad deberán ser parte del protocolo de investigación. 9,52 En el cuadro 9 se muestra una propuesta de las distintas categorías de eventos adversos que deben identificarse en los participantes de un ECCA. 9 Todo conocimiento que tengan los investigadores acerca de los posibles riesgos o eventos adversos que se detecten y que están relacionados con la intervención …”
Section: Monitoreo De Seguridadunclassified